2014
DOI: 10.1002/2014wr015574
|View full text |Cite
|
Sign up to set email alerts
|

Saltwater‐freshwater mixing dynamics in a sandy beach aquifer over tidal, spring‐neap, and seasonal cycles

Abstract: The biogeochemical reactivity of sandy beach aquifers is closely linked to physical flow and solute transport processes. Thus, a clearer understanding of the hydrodynamics in the intertidal zone is needed to accurately estimate chemical fluxes to the marine environment. A field and numerical modeling study was conducted over a 1 year timeframe to investigate the combined effects of tidal stage, spring-neap variability in tidal amplitude, and seasonal inland water table oscillations on intertidal salinity and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
159
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(175 citation statements)
references
References 83 publications
16
159
0
Order By: Relevance
“…Under these hydrologic conditions, the saline circulation cell and its associated mixing zone are spatially limited, and the inland hydraulic gradient is the main control of total SGD (Heiss and Michael, 2014;Robinson et al, 2007a). Based on the stable isotopes of water along the STE, Chaillou et al (2017) confirmed the contribution of only two water endmembers (i.e.…”
Section: Study Areamentioning
confidence: 94%
See 1 more Smart Citation
“…Under these hydrologic conditions, the saline circulation cell and its associated mixing zone are spatially limited, and the inland hydraulic gradient is the main control of total SGD (Heiss and Michael, 2014;Robinson et al, 2007a). Based on the stable isotopes of water along the STE, Chaillou et al (2017) confirmed the contribution of only two water endmembers (i.e.…”
Section: Study Areamentioning
confidence: 94%
“…tidal and wave pumping, hydrography, and density) induce temporal and spatial variability in biogeochemical conditions (see Santos et al, 2012, and references therein). The mixing zone is subject to oscillating conditions, with rapid changes in oxygen saturation, redox potential and organic matter input controlled by tidal stage and amplitude, sea level and seasonal water table fluctuations (Abarca et al, 2013;Gonneea et al, 2013;Heiss and Michael, 2014;Robinson et al, 2014). These physical processes are likely to impact the distribution and biogeochemical reactivity of many dissolved constituents (Beck et al, 2007;Kroeger and Charette, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…SEAWAT has been developed by the United States Geological Survey (USGS), and numerous studies have used the code to simulate variably-density, transient groundwater flow (Heiss and Michael, 2014;Herckenrath et al, 2011;Rasmussen et al, 2013). In SEAWAT the governing flow and solute transport equations are coupled and solved with a cell-centred finite difference approximation.…”
Section: Variable-density Groundwater Modelmentioning
confidence: 99%
“…These studies can be classified into two categories: field or laboratory experiments and analytical or numerical models. Field or laboratory experiments rely on measurements to delineate the hydrodynamics of near-shore aquifer systems (e.g., Westbrook et al 2005;Trefry et al 2007;Kuan et al 2012;Heiss and Michael 2014), whereas analytical or numerical models solve governing equations that can approximately reproduce system responses according to input parameter variations (Ataie-Ashtiania et al 1999, 2001Mao et al 2006;Werner and Lockington 2006;Li et al 2008;Bakhtyar et al 2013). The greatest challenges hindering most experimental approaches involve obtaining sufficient data for resolving detailed mechanisms of flow and transport among various scales of interest.…”
Section: Introductionmentioning
confidence: 99%